2021
DOI: 10.3390/atmos12070888
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurrence of Marine Extremes Induced by Tropical Storms and an Ocean Eddy in Summer 2016: Anomalous Hydrographic Conditions in the Pacific Shelf Waters off Southeast Hokkaido, Japan

Abstract: This study proposes an analysis methodology to address how very rare marine extremes can be understood using limited data. In summer 2016, extreme weather and marine events occurred simultaneously around the Pacific shelf off southeastern Hokkaido, Japan. Six successive tropical storms brought extreme precipitation and an anticyclonic mesoscale eddy of subtropical Kuroshio water closely approached the coast, locally causing marine heat waves. We examined how these compound extremes affected oceanographic condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…It is here emphasized that sea surface salinities simulated by the 1/50° ocean model had low-salinity bias of about 0.2 in autumn around the focal region (e.g., [25]), which was reconfirmed by comparison with in situ sea surface salinities along the A-line (e.g., [22]) that were measured on 4-10 October 2021 (not shown).…”
Section: Relationships To Environmental Conditionssupporting
confidence: 56%
See 3 more Smart Citations
“…It is here emphasized that sea surface salinities simulated by the 1/50° ocean model had low-salinity bias of about 0.2 in autumn around the focal region (e.g., [25]), which was reconfirmed by comparison with in situ sea surface salinities along the A-line (e.g., [22]) that were measured on 4-10 October 2021 (not shown).…”
Section: Relationships To Environmental Conditionssupporting
confidence: 56%
“…Meanwhile, subtropical, oligotrophic waters are transported from the subtropics to the study region, mainly through two pathways (Figure 1). Soya Warm Current water is supplied seasonally from the Sea of Okhotsk during summer-autumn by a downstream extension of the Soya Warm Current [23][24][25]. This water originates in the Kuroshio, which bifurcates south of Kyushu, intrudes into the Sea of Japan, flows northward as the Tsushima Warm Current, and reaches the Sea of Okhotsk.…”
Section: Satellite-derived Datamentioning
confidence: 99%
See 2 more Smart Citations
“…A MHW known as "the blob," which occurred persistently in 2014-2016 in the northeastern Pacific, is especially famous (e.g., [16]). In contrast, a search for studies conducted in the northwestern Pacific, particularly east of Japan, with the keyword "MHW," yielded only three scientific studies [17][18][19]: one conducted in subtropical waters [17] and the others in subarctic waters [18,19]. Miyama et al [18] reported the occurrence of MHWs in summer during 2010-2016 near Hokkaido, northern Japan, which they attributed to warm mesoscale eddies that had become detached from the subtropical Kuroshio Extension and had been advected into the subarctic Oyashio region every summer of that period.…”
Section: Introductionmentioning
confidence: 99%